Mengasah Potensi Kepribadian Anak melalui Pendekatan Komunikasi Positif - Ahmad, Nur (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Positive communication is communication that is able to develop its positive potency of children. Positive communication is built to form the fabric of a child’s personality that will also be established between parents and children. It can cultivate emotional intelligence. Of course, these two things will make a valuable provision for children’s development in the future. While missed communication would cause them uneducated and ignorant. Failure in communicating wouldnormally make a child called weird or crazy. Actually there are a few tips to succeed in realizing the potency of the child’s qualified personality, such as provide exemplary son, make the house as a science park, provides a vehicle for creativity, avoid negative emotions and always pray for children to be always given a good personality and mental health. Later in the development potency of the child’s personality can also be affected by a variety of factors. One of them is the positive communication patterns of parents towards their children (get them to always communicate in a positive environment). If the communication patterns of parents are bad, the negative impact will be felt by the child as well.